Level of self-esteem among late adolescents and early Adults at the College of Education, University of Hail, Saudi Arabia - Fadulelseed Ahmed Fadulelseed, Osman (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2021)
The current research aims to identify the level of self-esteem of late adolescents and early adults at the College of Education, University of Hail, Saudi Arabia, in the academic year (2017-2018) in light of gender and age. To achieve this, the researcher used the Causal Comparative Method through applying the (Cooper Smith, 1967) scale after checking the psychometric properties, as a tool to collect data from a random sample of (130) late adolescents and early adults. To analyze the data, the researcher used the (SPSS) program through the T-test for one sample and the T-test for two independent samples, Two-way analysis of variance. The results indicated; high level of self-esteem among late adolescents and early adults, there are differences in male and female self-esteem in favor of males, there were differences in self-esteem between late adolescents and early adults in favor of early adults, there is no variances in self-esteem Attributed to the interaction of age stage and gender. In conclusion, the researcher recommended designing a counseling program to reinforce self-esteem among females and late adolescents, and he also suggested investigating the relationship between self-esteem, critical thinking and creative thinking among students of the College of Education at the University of Hail.